Outcomes of A Single-Stage Triple Procedure for The Treatment of Developmental Dysplasia of the Hip in Children of Walking Age. (Journal of Pakistan Orthopaedic Association, 2024)
Objective: To evaluate the radiographic and functional outcomes of treating DDH in ambulatory children using single-stage triple surgery, combined with open reduction, femoral varus derotational osteotomy and Salter’s innominate osteotomy.Methodology: The Department of Orthopaedic Surgery of the Sheikh Khalifa Bin Zayyad Al Nayyan Medical Complex Quetta conducted this descriptive study between January 2017 and December 2020. The study included of 60 patients (96 hips) aged between 18 months and 8 years who were diagnosed with DDH. Severin’s classification was applied to assess radiologic outcomes, while McKay’s criteria were used to evaluate clinical outcomes.Results: The majority of patients (58.3%) of this study had hips with severe dysplasia (Tönnis Grade IV) preoperatively, with a mean age of 4.6 years. The final procedures performed were Salter’s innominate pelvic osteotomy in 84 hips (87%), Pemberton osteotomy in 8 hips (8.3%), and Chiari’s salvage procedure in 4 hips (4.1%). According to McKay’s criteria, the postoperative results were excellent in 45 patients, good in 8 patients and fair in 5 patients. Radiographically, 84 hips had a type I and 10 hips a type II of the Severin classification.Conclusions: In particular, severe DDH with walking age group is best treated by single-stage triple procedure. This method yields excellent to good functional and radiographical results. Early recognition and treatment also continue to be important aspects in managing challenging dysplastic hips.